The twelfth international workshop on collaborative editing systems - Agustina (2013)
Collaborative editing (CE) is an area of continuous research since early days of CSCW. Various CE systems have been studied in academia as research vehicles to investigate key technical issues in building advanced collaborative applications, and an increasing number of real-world CE systems are being developed in industry as Internet/Cloud-based CE systems/services, such as Google Docs/Wave, Subethaedit, CodoxWord, and IBM OpenCoWeb. This workshop aims to bring together CE academic researchers, industry developers, and end-users to discuss and exchange ideas on contemporary issues in researching, developing, and adopting CE systems. We have successfully organized this workshop annually at CSCW-related conferences. As CE systems are reaching more end-users, this year's workshop will, in addition to discussing classic CE technical topics, extend to cover issues that affect end-users' adoption of CE systems in their work such as privacy, security, usability, and social impacts of CE systems.